Economic efficiency in the manufacturing sector an inter-regional comparison: Brazil, 1970 - Almeida, Manoel Bosco de (1981)
This dissertation in an attempt to measure the economic efficiency of Brasil's manufacturing sector at the two-digit level of aggregation and lower. More specifically, we investigate some of the reasons for the sizeable differences in labor productivity between the manufacturing sectors of the Northeast and the South of Brazil. We investigate how the observed differences in average labor productivity between the two regions could be explained by differences in the capital/labor ratio and economies of scale. The question we ask is: what would the Northeast's level of average labor productivity have been if either this region's capital/labor ratio and/or the average plant size were the same as the South's. One point of time, 1970, is chosen since it is the most recent year for which complete data are available. First, we estimate the effect of capital / labor ratio differences on productivity differences. For this estimation, a production function was specified. The quality of the data and the limited number of observations per sector and branch restricted our choice to the CES production function. Information on the Northeast's relative efficiency, defined as the ratio of the Northeast's hypothetical labor productivity to the South's actual level, show that the capital / labor ratio by itself did not explain the observed differences in average labor productivity either at the two-digit or lower level of aggregation. Adjustment for the level of capacity utilization and / or changes in the values of the elasticity of substitution did not change this outcome much. Next, the Northeast's relative efficiency was adjusted for economies of scale. This masure was called the North-east's adjusted relative efficiency. This adjustment indicated increasing returns to scale for some sectors and constant returns to scale for others. IN either case, however, the unexplained residuals remained large for the majorty of sectors. Of the two adjustments, the K / L ratio accounted for the major increase in ratio efficiency and perhaps would be more effective in reducing the sizeable across-region differences in labor productivity than would increasing the scale of plants. This Suggests that mediu - and small-scale plants might play a more effective role in the North-east's economic developmente. Data and time limitations prevented any further analysis of this or other relevant issues.